Exploring Thailand’s Wellness Economy: Opportunities for Expansion and Major Challenges - Seenprachawong, Udomsak (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2025)
This study presents a comprehensive analysis of Thailand’s wellness industry, examining its value chain, competitive positioning, and potential for growth. By integrating in-depth interviews with 23 key informants and secondary data covering the period from 1999 to 2025, the study identifies Thailand’s core strengths-including internationally accredited medical standards, unique cultural offerings, and competitive pricing-as well as opportunities driven by an aging population, rising health awareness, and supportive government policies. Key challenges, such as language barriers, safety concerns, workforce limitations, and inconsistent business reputations, are also highlighted, underscoring the need for strategic planning in a competitive global context. Thailand’s initiatives in public–private collaboration, ASEAN regional integration, and innovation across medical services, health products, education, and traditional medicine demonstrate a strong commitment to becoming the region’s leading wellness hub. Leveraging its natural and cultural assets, Thailand should aim to offer holistic wellness experiences while strengthen skills, safety, infrastructure, and innovation to attract international travelers and build a sustainable, globally competitive wellness industry.